3-(2-Hydroxyethyl)-1-(4-nitrophenyl)-1H-benzo[d]imidazol-3-ium bromide - Halliru Ibrahim; Sizwe J. Zamisa; Muhammad D. Bala; Pinkie Ntola; Holger B. Friedrich (IUCrData)
The cation of the title salt, C15H14N3O3+·Br−, has a dihedral angle of 24.26 (6)° between its fused imidazole and 4-nitrophenyl rings and the N—C—C—O torsion angle associated with the hydroxyethyl substituent is 60.15 (17)°. In the crystal, the bromide ions act as double acceptors for hydrogen bonds from a hydroxyl group (O—H...Br) and a fused imidazolium moiety (C—H...Br). Additionally, C—H...O hydrogen bonds between the phenyl group and hydroxyl oxygen atom create a two-dimensional supramolecular network extending diagonally in the crystallographic bc plane.